A STUDY OF COUNTERFACTIVE MARKERS IN ENGLISH VERSUS VIETNAMESE - Ph. D. Ngũ Thiện Hùng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis discussed the semantics and pragmatics of counter-factive markers. The study explored the use of English and Vietnamese counter-factive markers in novels and short stories reference. The study was carried out through the adoption of qualitative, contrastive approaches to examine grammatical and lexical devices signaling the meaning of counter-factivity. These lexical devices were used to mark a speaker's conclusion on the possibility of the states of affairs and to modify the illocutionary force of his/ her assertion in appropriate contexts. The most important and significant aspect of the study, the similarities and differences between English and Vietnamese ways of expressing counter-factiviy in the view of semantics and pragmatics, was presented in order to help learners have better use of counter-factive markers in communication. This thesis also provided a procedure that uses this information to give the interpretation for counter-factive markers in English and Vietnamese.